2008
DOI: 10.1007/s10384-008-0594-y
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler imaging of the superior ophthalmic vein in different clinical forms of Graves’ orbitopathy

Abstract: SOV was significantly reduced in orbits with congestive GO or with myogenic fibrotic GO, but not in orbits with fibrotic lipogenic orbitopathy. SOV congestion may be a contributing pathogenic factor in both congestive and fibrotic myogenic Graves' orbitopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
3
22
0
2
Order By: Relevance
“…The evaluation of the venous flow can also be useful. Monteiro et al (66) reported that patients with congestive orbitopathy and predominantly myogenic fibrotic GO experience a significant reduction in the SOV flow, matching reports from other authors (81) and supporting the idea that orbital congestion due to extraocular muscle enlargement can reduce orbital venous drainage. Because DON is known to be related to orbital apex crowding, the existence of severe venous stasis in the orbits possibly reflects a stage in its development.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The evaluation of the venous flow can also be useful. Monteiro et al (66) reported that patients with congestive orbitopathy and predominantly myogenic fibrotic GO experience a significant reduction in the SOV flow, matching reports from other authors (81) and supporting the idea that orbital congestion due to extraocular muscle enlargement can reduce orbital venous drainage. Because DON is known to be related to orbital apex crowding, the existence of severe venous stasis in the orbits possibly reflects a stage in its development.…”
Section: Introductionsupporting
confidence: 55%
“…Several studies have compared the orbital blood flow in GO patients and control subjects (25),(64),(65), as well as in patients with different clinical forms of GO (66). Benning et al (64) found that the flow velocity in the right ophthalmic artery was much greater in subjects with clinically active GO than control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Congestion of the superior orbital vein plays an important role in the inflammatory phase, as demonstrated by computed tomography (19,20,21) and color Doppler imaging studies (22,23,24,25). It has been suggested that in GO the success of the immunosuppressive treatment is the result of the effect not only on the autoimmune process but also on the reduction of orbital venous congestion.…”
Section: Chronic Congestive Gomentioning
confidence: 99%
“…1 The enlargement of the extraocular muscles is responsible for most of the debilitating manifestations of the disease, including proptosis, diplopia, congestive signs, and DON. [2][3][4][5] DON is a serious complication of GO occurring in 3.4% of patients, 6 almost always as a result of optic nerve compression at the orbital apex by enlarged extraocular muscles. The diagnosis of DON rests mainly on clinical findings such as decreased VA, abnormal VFs, altered color and brightness perception, delayed visual evoked potentials, afferent pupillary defects, and edema or atrophy of the optic nerve head.…”
mentioning
confidence: 99%